Ray-finned fishes (Osteichthyes, Actinopterygii) from the type maastrichtian, the Netherlands and Belgium - Friedman, M (2012)
Ray-finned fishes are a diverse, but understudied, component of the Maastrichtian marine fauna of the southeast Netherlands (Limburg) and northeast Belgium (Li?ge-Limburg). The most extensive reviews of fishes from these uppermost Cretaceous deposits were made in the early and mid-Twentieth Century, but little research on this important assemblage has been executed since. The present paper provides figures and brief descriptions of fishes from the Maastrichtian type area as an aid for field identification of fossil discoveries. A simple key to common Maastrichtian fish teeth from this area is also included. All convincing records of ray-finned fishes from the Maastrichtian of the Netherlands and Belgium, inclusive of the Mons Basin, are teleosts, and include both stem- and crown-group members. Higher teleost clades reported here are: Pycnodontiformes (Pycnodontidae), Pachycormiformes (Pachycormidae), Aspidorhynchidiformes (Aspidorhynchidae), Ichthyodectiformes (Saurodontidae), Pachyrhizodontoidei (Pachyrhizodontidae), Aulopiformes (Apateopholidae, Cimolichthyidae, Dercetidae, Enchodontidae), Polymixiiformes (Polymixiidae), Trachichthyiformes (family incertae sedis) and Tetraodontiformes (family incertae sedis).